In situ catalyzed poly(ε-caprolactone)/organic rectorite nanocomposites with excellent electrochemical performance - Limin You; Shifan Zhang; Zhuoxiong Huang; Wanle Pi; Jiaqi Liu; Rui Ma (eXPRESS Polymer Letters, 2023)
In recent years, solid polymer electrolytes (SPE) has attracted much attention because of its good safety and environmental stability, among which poly(ε-caprolactone) (PCL) based solid electrolyte film is one of the most potential materials. We have adopted the method of synthesizing polymer nanocomposites with natural clay, which can effectively meet the needs of electrolytes. In this study, cetyl trimethyl ammonium bromide (CTAB) was used to modify rectorite (REC), and the ε-CL monomer is inserted between the rectorite silicate layers. PCL/organic rectorite (OREC) nanocomposites were synthesized by in situ intercalation polymerization. The yield of the polymer nanocomposite could reach 93.6% when the molecular weight of the polymer nanocomposite was 39 000. The effects of OREC addition on the morphology, thermal stability, and electrochemical properties of PCL/OREC nanocomposites were investigated by various characterization methods. The temperature can be increased by 50 °C when the thermal decomposition is 50 wt%, and the crystallinity decreases by 4.6%. Composite polymerelectrolytes (CPEs) (PCL/OREC) showed a good electrical conductivity of 1.13·10–4 S·cm–1 at 60 °C and an excellent capacity retention rate of 96.7% after 100 cycles at 0.5 C current density. This study has important guiding significance for the development of polymer nanocomposites as solid electrolytes.